Progesterone and progestins: neuroprotection and myelin repair - Schumacher, Michael (2008)
Progesterone, known for its role in pregnancy, also exerts marked effects on the nervous system. Its neuroprotective and promyelinating actions, now well documented by experimental studies, make it a particularly promising therapeutic agent for neuroinjury and neurodegenerative diseases. This concept has recently been translated into clinical practice, though there is need for more experimental studies and investigations on the mechanisms of the actions of progesterone. However, it is important to be aware that most of the experimental research concerns the effects of physiological progesterone. Although progesterone represents an interesting therapeutic option, the recognition of its beneficial effects on the nervous system also suggests novel therapeutic benefits for some synthetic progestins derived from progesterone, currently used for contraception or in postmenopausal hormone replacement therapies (HRTs).